Influence Analysis of Phase Angle of Double Cross Universal Joint Steering Transmission Shaft - Li Ning; Li Yourong; Zhou Sizhu; Zeng Yunyun (Jixie chuandong)
Aiming at the problem of the installation space of double cross universal joint steering transmission shaft is limited,it is difficult to meet the condition of constant speed drive,and need to adjust the phase angle to reduce the rotating speed fluctuation,the rotating speed ratio and rotating angle equations of steering transmission shaft are established by means of spatial geometric projection method,and the equation is verified by using the constant velocity condition. The influence of phase angle on rotating speed ratio are quantitatively analyzed,the results show that the input shaft and output shaft can realize constant speed drive while two transmission angle are equal and the phase angle is equal to the transmission plane angle,and the double cross universal joint transmission shaft can’t realize the constant speed drive while two transmission angle are not equal.However,the speed difference of input shaft and output shaft is the smallest while the phase angle is equal to the transmission plane angle. Therefore,this is the best phase angle when phase angle is equal to transmission plane angle and their phases are reversal. Then,the optimal solution formula of phase angle is deduced based on hard point of steering system and the computer program is compiled. The calculation result of the program is accurate by example verification. The conclusion and the program has theoretical and practical significance on system design of automobile steering and research on the transmission of other types universal joint.